Identificación de la entomofauna en el Transecto N° 6 parte A cantón La Maná, Provincia Cotopaxi, 2017. - Oña Marca, Cristian Santiago (2017)
SUMMARY The objective of this researchwork is to relate a collection of insects in the area for its classification and to determine the effect of deforestation on the composition of entomofauna (micro fauna) of Santa Rita Parish of La Maná Canton, which was delimited by using a GPS to study the area or transect whose surface is one hectare, the transect is located in the following coordinates: Length: 79 ° 08'05.74 ''S, Latitude: 1 ° 0'22.72''W, and An altitude of 659 masl For the insect collection PitFall drop traps were placed at 10 points of the random transect, a total of 2926 individuals were collected, corresponding to 42 families identified, determining that there are seventeen dominant families with a number of individuals greater than 10, which represents an index of Shannon equivalent to 0.51291028, through simple statistical analysis it was concluded that there is no significant difference in relation to diversity so, there is a homogeneous diversity. The information obtained from this project serves as the first approximation to the entomological diversity of the transect studied, however, it is recommended to use different types of traps and diversity calculation indexes to obtain more extensive information about the emntomofauna of the place.